Adsorption study on Moringa Oleifera Seeds and Musa Cavendish as natural water purification agents for removal of lead, nickel and cadmium from drinking water - A Aziz, N A; Jayasuriya, N; L, Fan (IOP Publishing, 2015)
The effectiveness of plant based materials Moringa oleifera (Moringa) seeds and Musa cavendish (banana peel) for removing heavy metals namely lead (Pb), nickel (Ni) and cadmium (Cd) from contaminated groundwater was studied. Tests were carried out with individual and combined biomass at neutral pH condition on synthetic groundwater samples. The optimum biomass doses were determined as 200 mg/L for single biomass and 400 mg/L (in the ratio of 200 mg/L: 200 mg/L) for combined biomasses and used for adsorption isotherm studies with contact time of 30 minutes. Results showed that combined biomasses was able to met the Pb, Ni and Cd WHO standards from higher Pb, Ni and Cd initial concentrations which were up to 40 µg/L, 50 µg/L 9 µg/L, respectively compared to individual biomass of Moringa seed and banana peel. Moringa seeds exhibited the highest removal of Pb (81%) while the combined biomasses was most effective in removing Ni (74%) and Cd (97%) over wider their initial concentration ranges. The experimental data were linearized with Langmuir and Freundlich adsorption isotherm models. Freundlich model described the Pb adsorption better than the Langmuir model for all the tested biomasses. However, the Langmuir model fit better with the experimental data of Ni adsorption by Moringa seeds. Both models showed negligible differences in the coefficient of determination (R2) when applied for Ni and Cd adsorption on banana peel and combined biomasses, suggesting that there were multiple layers on the biomass interacting with the metals. Chemisorption is suggested to be involved in Pb adsorption for all tested biomasses as the value of nF calculated was lower than one. This type of adsorption could explain the phenomenon of different behavior of Pb removal and the higher Pb adsorption capacity (represented by KF values) compared to Ni and Cd. The study demonstrates that Moringa seeds, banana peel and their combination have the potential to be used as a natural alternative to the other water treatment agents for removing the Pb, Ni and Cd from drinking water.